2014
DOI: 10.11648/j.ijass.20140202.11
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Study of Neutron Star Glitches

Abstract: Neutron star glitches; spanning a period of 42 years of pulsar timing were studied. These glitches are from Radio, X-ray, Anomalous X-ray and Milliseconds Pulsars. Radio Pulsars dominates the glitch events, contributing 87% of the glitches. Pulsars of characteristic age bracket 10 3 to 10 5 yrs dominated the glitch events, at a rate of 5.2 glitches per year per pulsar. Pulsar of the above age bracket exhibits large size glitches compared to others. A large frequency spin-up (△v) is generally associated with la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
(16 reference statements)
4
2
0
Order By: Relevance
“…There is a predominance of small glitches according to the authors for > 10 yr and <103 yr; and no large glitch has been reported for > 10 yr. This was corroborated by the report that large glitches are mostly exhibited by pulsars with characteristic age between 10 3 to 10 5 yr [12]. The glitch size distributions are consistent with power laws with the index varying from pulsar to pulsar [15].…”
supporting
confidence: 84%
See 4 more Smart Citations
“…There is a predominance of small glitches according to the authors for > 10 yr and <103 yr; and no large glitch has been reported for > 10 yr. This was corroborated by the report that large glitches are mostly exhibited by pulsars with characteristic age between 10 3 to 10 5 yr [12]. The glitch size distributions are consistent with power laws with the index varying from pulsar to pulsar [15].…”
supporting
confidence: 84%
“…It was shown that Vela pulsar, J0537-6910 and J1341-6220 show a quasiperiodic glitch pattern [15]. Vela alone was reported to have quasiregularly pattern [18], and a linear glitch pattern was also reported for Vela and J0537-6910 depicting also strong elasticity of the objects [12]. This corroborated the report that Vela and J0537-6910 have particular glitching behaviours or pattern and that such pattern may be shared by most Vela-like pulsars [11].…”
supporting
confidence: 81%
See 3 more Smart Citations